EFFECT OF EFFERVESCENCE IN COMBINATION WITH SUPERDISINTEGRANTS IN THE FORMULATION OF PROPRANOLOL HCL ORAL DISINTEGRATING TABLETS - Thulluru, Ashok; Sai KUMAR, Veeravalli; M, Pavan Kumar; B, Roshitha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: The current research work is intended to formulate propranolol HCl (PLH) as orally disintegrating tablet (ODT). It is also intending to check the superiority in a combination of superdisintegrants and effervescent mixture than the use of superdisintegrants alone by a direct compression technique. To fasten the onset of action and thereby enhancing the bioavailability of PLH in comparison to its conventional tablets. Methods: Standard calibration curve of PLH was obtained in pH 6.8 phosphate buffer by spectrophotometric method, drug-excipient compatibility studies were carried by Fourier transform infrared (FT-IR) studies. All the formulations were evaluated for pre and postcompression studies. Accelerated stability studies were carried out up to 6 months for the optimized formulation, EF3. Results and Discussion: Superdisintegrants used in the study are compatible with PLH. Pre- and post-compression parameters were within the acceptable limits for all formulations. In vitro dissolution kinetic studies indicate the release of PLH from ODT increases as the concentration of superdisintegrants as well as the ratio of citric acid: NaHCO3 of effervescent mixture increases. Formulations with an effervescent mixture are having rapid disintegration and dissolution rate when compared to the formulations with superdisintegrants alone. The order of superdisintegrants in enhancing the dissolution rate of PLH is crospovidone (CPV) > croscarmellose sodium (CCS) > sodium starch glycolate (SSG). Formulation, EF3 (10% CPV and 1:3, citric acid: NaHCO3 ratio, respectively) had the highest dissolution efficiency at 10 minutes (DE10=82.74%); the first order dissolution rate constant (K1=0.141/minutes) with a regression coefficient (r2=0.974) and lesser time for 90% of drug release (t90=4 minutes), was considered as the optimal ODT in this study. Formulation EF3, passed the test for stability. Conclusion: Hence, an effective PLH ODT was formulated by the direct compression technique with disintegration by combination of superdisintegrants and effervescent mixture, will fasten the onset of action and enhances the bioavailability of PLH in comparison to its conventional tablets. Keywords: Propranolol HCl, Orally disintegrating tablet, Sodium starch glycolate, Croscarmellose sodium, Crospovidone, Direct compression, In vitro dissolution studies.